TAFSIR SAINTIFIK TENTANG PUASA RAMADHAN - M. Dalip (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
This article describes the scientific interpretation of Mahmud Yunus to the verses of the Qur'an in the interpretation of the Qur'an. He seeks to maintain the harmony of the Qur'an with science while showing the readers that modern scientific discoveries have been stated or hinted at in the Qur'an. Mahmud Yunus's scientific interpretation in his commentary does not follow the model as has been adopted by other popular scientific interpreters, such as Tantawi Jauhari. In interpreting the Qur'an scientifically, Mahmud Yunus took his own style. He tried to avoid the scientific explanation by each word. He only explained the verses of the Qur'an and then related them to the development of modern science. Mahmud Yunus's style of interpreting the Qur'an will be seen when interpreting the QS. surah al-Baqarah / 2 verses 183-185. For Mahmud Yunus, linking the Qur'an with scientific knowledge is one of the efforts to encourage Muslims to master modern science, and can arouse Muslims' passion to advance and catch up to later be aligned with the western world.